Síntese e caracterização de nanofios de prata através do processo poliol - Stradolini, Cristiano Jaeger (2018)
During the past few years, nanosized noble metals have attracted much attention due to their unique electrical and physical properties. Among them, silver has been the subject of several studies, by having the highest electrical and thermal conductivity between all metals. For that reason, its one-dimensional nanometric structure (nanowires) has been receiving a lot of attention, due to its potential in the manufacture of devices that offer good electrical conduction and optical transparency. There are several methods of synthesis for the production of these silver nanowires, however the most widely used is the polyol process, due to its simplicity and low cost. Several studies show the influence of different parameters of the polyol process (reaction time, temperature and etc.) on the final morphology of the nanowires. Thus, a well-defined protocol of good practice for obtaining long and thin silver nanowires is required. The main objective of this work is the development of a low cost protocol capable of generating nanowires with great lengths by modifying the polyol process parameters. Variations were also performed in the method of addition of the main synthesis reagent, silver nitrate, and its influence on the final morphology of the silver nanowires was studied. In this work, by using the polyol process, nanowires up to 40 μm in length were reported, demonstrating the effectiveness of the developed technique and conclusions about the final results were presented.